Dialektika Hukum dan Kekuasaan - salman luthan (Fakultas Hukum Universitas Islam Indonesia, 2000)
The legal essence can be viewed from several perspectives; authority, substance, sociology and reality. Power is an interaction concepts and social interrelation existing in societies, nation, and human beings. The continuing discussion of legal power and authority appear within two patterns ofrelationship; law is an equivalent to authority; and law is different from authority. The legal symbiotic relation with power results functional relation. Authority hasa certain function toward law and vice versa. Power plays a role as an instrument to form, enforce, and execute the law. Law functions to legitimate and justify power.